How useful is virtual reality? A mixed-method study on student teachers’ perceptions - Hickethier, Florentine; Gröschner, Alexander; Dehne, Mathias; Ader, Engin; Michalsky, Tova (Frontiers in Education, 2026)
Virtual reality (VR) as a form of simulation-based learning can lead to better understanding of learners and increase motivation. Recent evidence shows effectiveness in teacher education in terms of skill growth for student teachers. In this regard, the perceived usefulness of a novel technology is a key factor affecting behavioral intention to use it. Therefore, this mixed-method study investigates the perception of the usefulness of a VR environment from the perspective of student teachers and explores to what extent the change in perception affects the intention to use it in later professional practice. To answer the questions, N = 57 student teachers from four countries assessed a VR environment designed for teaching mathematics. The VR environment deals with the spread of infectious diseases to address the mathematical issue of exponential growth. To assess its usefulness as well as its general potential, students filled in a questionnaire before and after the VR simulation and participated in an interview afterwards. The findings show a significant positive change in usefulness beliefs. Furthermore, perceived usefulness predicted intention to use the VR technology. Results from the interviews show the potential of the new technology in transcending certain boundaries of everyday teaching and emphasize on the affective component of a VR experience in schools. But also limitations for every day life and use of VR, for instance, with regard to specific age groups were mentioned. A main implication of this study is that an early experience of VR in teacher education underlines the willingness to use this technology in later professional life.